THE USE OF PROBABLE PASSAGE STRATEGY ON STUDENTS' ABILITY TO WRITE A NARRATIVE TEXT - Yustika, Ariani; Vonti, Lungguh Halira; Suryanti, Yanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
Writing is one of the language skills that needs to be learned by students in English subject. It is an important part of communication. Students are expected to be able to write the narrative text into some paragraphs with the chronological sequences. However, students still have difficulties to find the idea and to write the narrative text because of their lack of understanding grammar and vocabularies. Probable passage strategy is an appropriate strategy to solve the problems. The aim of the research is to investigate the effect of using probable passage strategy on students ability in writing a narrative text. The research was conducted to the eighth grade of SMP PGRI 16 Bogor. In conducting this research, the writer applied pre-experimental method and chose one group pre-test and post-test design. There were 26 students from class VIII-C taken as the sample by using random sampling as technique sampling of this research. The data were taken from two tests; pre-test and post-test. The data were analyzed by using t-test formula. Based on data calculation, she found the result of t-test value is 11.98. Meanwhile, t-table value is 2.06 at significant level 0.05 with the degree of freedom (df) is 25. It shows that the t-test value is higher than t-table value (11.98 more than 2.06). It means the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the use of probable passage strategy affects students ability to write a narrative text.